Curbing “Dark” Activity at Sea: The Role of the Marine Insurance Industry - Priyal Bunwaree (European Journal of Risk Regulation)
Some fishing vessels breach maritime laws by operating with their mandatory tracking systems (Automatic Identification System (AIS)) switched off. Marine insurers act as enablers of this practice since these vessels cannot operate without insurance. This article explores why insurers in England take on the risk of insuring them and assesses how the insurers are operating against the regulatory framework in doing so. It identifies the solutions that could raise standards in marine insurance and lead to increased legal compliance by the insured vessels. This would consequently enhance maritime safety, while increasing transparency in fisheries across all oceans. Importantly, by discouraging vessels from going dark, any illegal activities underlying the non-transmission of AIS data, such as human, drug or weapon trafficking, illegal fishing or sanctions evasion, would also be curbed.